Early childhood teachers’ perception of the attitudes and behaviors of a professional teacher - Khoiriyah, Khoiriyah; Hidayati, Kuni Hikmah; Kartika C., Wuri (Journal of Early Childhood Care and Education, 2024)
Teachers’ perceptions regarding their professional identity affect their teaching efficacy, their professional development, their propensity to stay in the teaching profession, and their ability and willingness to enhance their teaching performance and cope with educational change. This study aims to explore the perceptions of Early Childhood Teachers related to the attitudes and behaviors of a Professional Teacher. Quantitative and qualitative approach were used. Data were collected through open-questionnaires and interviews. The subject in this study consists of 100 Early Childhood teachers in Jember who are now teaching in Aisyiyah Kindergarten. All the 100 teachers filled out the questionnaire, but only some were willing to be interviewed. The data were analyzed using Descriptive Statistics. The results of the study revealed that according to teachers’ perceptions, professional attitudes and behaviors include expertise, social ability, self-integrity and productive behavior. The study also found that most teachers rated themselves significantly low in terms of professionalism. Only those with more experience rated themselves high.